Efficacy and safety of Nivolumab in patients with advanced esophageal, gastroesophageal, and gastric cancers: a meta-analysis of randomized controlled trials. (2nd January 2023) - Oyenuga, Mosunmoluwa; Mohamed, Mohamed M. G.; Sartaj, Sara; Patel, Rushin; Oyenuga, Abayomi; Sen, Sandeep
Abstract: Background: Immune checkpoint inhibitors (ICI) have revolutionized care in oncology with improved overall survival in several cancer populations. Nivolumab has recently been approved for use in patients with upper gastrointestinal cancers. We quantitatively summarized the efficacy and safety of Nivolumab use in patients with advanced esophageal, gastroesophageal, and gastric carcinoma compared to standard chemotherapy. Methods: Systemic search of electronic databases was performed to analyze phase III randomized controlled trials (RCTs) comparing Nivolumab versus standard chemotherapy in patients with advanced upper gastrointestinal cancers. Primary endpoints were overall survival (OS) and progression-free survival (PFS). Data were pooled using random effects model via RevMan 5.4 software. Results: Four RCTs with a total of 3369 patients and a median follow-up of 13 months were included. The patients' mean age was 61 ± 20 years, 74.6% were males, and 26% had ≥1% PD-L1 expression. Compared to the chemotherapy group, Nivolumab group had a significantly favorable OS and PFS [HR 0.81;95% CI (0.74, 0.89), p < .001], [HR 0.82;95% CI (0.69, 0.98), p = .03], respectively. Nivolumab significant effect was only in patients with ≥1% PD L1 expression [HR 0.72; 95% CI (0.58, 0.89), p < .001]. No statistical difference was detected between groups regarding serious adverse effects (AE) [OR 1.47; 95%CI (0.94, 2.31), p = 0.09]. Conclusions: Compared to standard chemotherapy, the use of Nivolumab in patients with advanced esophageal, gastroesophageal, and gastric cancers is associated with improved overall and progression-free survival, with similar rates of AE and AE leading to death. The improvement in survival was significant in patients with ≥1% PD L1 expression.